2020
DOI: 10.1186/s12944-020-01419-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between the alanine aminotransferase/aspartate aminotransferase ratio and new-onset non-alcoholic fatty liver disease in a nonobese Chinese population: a population-based longitudinal study

Abstract: Background The alanine aminotransferase (ALT)/aspartate aminotransferase (AST) ratio has been considered an alternative marker for hepatic steatosis. However, few studies have investigated the association of the ALT/AST ratio with non-alcoholic fatty liver disease (NAFLD) in nonobese people. Methods A total of 12,127 nonobese participants who were free of NAFLD participated in this study. The participants were divided into quintiles of the ALT/AST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 42 publications
4
46
0
7
Order By: Relevance
“…Model 4 adjusted for model 3 plus lipid metabolic markers (TG, HDL-C, and LDL-C). Additionally, considering that the correlation between the AAPR and NAFLD may be different under different conditions [ 4 , 5 , 11 ], the researchers also conducted an exploratory hierarchical analysis in some subgroups and checked the differences between different hierarchical groups by the likelihood ratio test to determine whether there was an interaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model 4 adjusted for model 3 plus lipid metabolic markers (TG, HDL-C, and LDL-C). Additionally, considering that the correlation between the AAPR and NAFLD may be different under different conditions [ 4 , 5 , 11 ], the researchers also conducted an exploratory hierarchical analysis in some subgroups and checked the differences between different hierarchical groups by the likelihood ratio test to determine whether there was an interaction.…”
Section: Methodsmentioning
confidence: 99%
“…NAFLD is generally thought to be caused by overweight and obesity [2,8], and in the past, related studies were mainly conducted in obese people. However, in recent years, an increasing number of studies have focused on non-obese NAFLD [9][10][11]. In a recent meta-analysis of more than 2 million people in 24 countries, nonobese people accounted for 40.8% of NAFLD patients globally [12], and in Asia, this situation seems to be more common [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It was believed that the AST/ALT ratio could help distinguish NAFLD from the alcoholic cause of liver disease, and the AST/ALT ratio was one of the best indicators to quantify liver fat infiltration. 15,[31][32][33] What's more, the AST/ALT ratio was one of the best predictors for IR in the Asian population, which was a prominent marker for metabolic syndrome and T2DM. 9,11,14,33,34 Liver enzyme markers, especially ALT and AST/ALT ratio, were the surrogate marker for incidence of T2DM and impaired fasting glucose (IFG) tolerance.…”
mentioning
confidence: 98%
“…15,[31][32][33] What's more, the AST/ALT ratio was one of the best predictors for IR in the Asian population, which was a prominent marker for metabolic syndrome and T2DM. 9,11,14,33,34 Liver enzyme markers, especially ALT and AST/ALT ratio, were the surrogate marker for incidence of T2DM and impaired fasting glucose (IFG) tolerance. 11,12,35,36 A cross-sectional study includes 8863 Korean participants conducted by Ko et al 12 showed that AST/ALT was negatively associated with the incidence of T2DM, which showed the same conclusion with our present cohort study.…”
mentioning
confidence: 98%
“… 12 This lab and BMI-based definition was used in addition to ICD coding because NASH and NAFLD are significantly underdiagnosed in the her, 13 , 14 and because elevated ALT is more specific for NAFLD/NASH than elevated AST. 15 …”
Section: Methodsmentioning
confidence: 99%